Exogenous Melatonin Improves Antioxidant Defense in Cucumber Seeds (Cucumis sativus L.) Germinated under Chilling Stress - Marta, Bałabusta; Szafrańska, Katarzyna; Posmyk, Małgorzata M. (Frontiers in Plant Science, 2016)
The relationship between exogenous melatonin applied into cucumber seeds during osmopriming and modifications of their antioxidant defense was studied. Accumulation of hydrogen peroxide, antioxidant enzyme activities and glutathione pool were investigated in embryonic axes isolated from the control, osmoprimed, and osmoprimed with melatonin seeds. Germinating cucumber seeds are very sensitive to chilling. Temperature 10ºC causes oxidative stress in young seedlings. Seed pre-treatment with melatonin seemed to limit H2O2 accumulation during germination under optimal condition as well as during chilling stress and recovery period. Melatonin affected SOD activity and its isoforms during stress and recovery period but did not influence CAT and POX activities. Thus it is possible that in cucumber this indoleamine could act mostly as a direct H2O2 scavenger, but superoxide anion combat via SOD stimulation. The GSH/GSSG ratio is considered as an indirect determinant of oxidative stress. When the cells are exposed to oxidative stress GSSG is accumulated and the ratio of GSH to GSSG decreases. In our research pre-sowing melatonin application into the cucumber seeds caused high beneficial value of GSH/GSSG ratio that could be helpful for stress countering. Glutathione reductase (GSSG-R) activity in the axes isolated from these seeds was two fold higher than in those isolated from the control and from the osmoprimed without melatonin ones. Additional isoforms of GSSG-R in melatonin treated seeds was also observed. It explains high and effective GSH pool restoration in the seeds pre-treated with melatonin. We confirmed that melatonin could protect cucumber seeds and young seedlings against oxidative stress directly and indirectly detoxifying ROS, thereby plants grown better even in harmful environmental conditions. This work is the first that investigated on plant in vivo model and documented melatonin influence on redox state during seed germination. This way we try to fill lack of information about melatonin-regulated pathways involved in antioxidant strategy of plant defence.